The Phenomenon of Distribution and Impact of Zakat: How is it Practiced in Muslim Societies - Maulana, Gempa; Sulfinadia, Hamda; Efrinaldi, Efrinaldi; Ringgit, Awang (Samara: Journal of Islamic Law and Family Studies, 2023)
Zakat, as an act of worship and a form of obligation for Muslims, has a crucial role in creating social justice and reducing economic inequality in Muslim communities. This research aims to provide a deeper understanding of how the zakat distribution process takes place. This type of research is empirical juridical research, namely by studying directly in the field to see directly how zakat is distributed, and the implications for the beneficiaries. The research results show that First The majority of people tend to view zakat only as an obligation that must be fulfilled by individuals, without understanding the potential positive impact it can have on the economic recovery of their fellow citizens; second, The practice of distributing zakat is carried out through an event called "mando'a," where zakat is distributed equally to all guests who attend the event; third, This research also found that the legal basis that requires every Muslim to pay zakat is contained in the Quran Surah At-Taubah verse 60, the words of Rasulullah SAW, and Law no. 32 of 2011 Article 25 concerning Zakat. However, even though there is a strong legal basis, the zakat funds received by Mustahik are insufficient to meet their needs. These funds are limited to daily needs, so they cannot have a significant long-term impact on their economic recovery. Thus, this research provides a clear picture of zakat practice, identifies differences between community perceptions and Islamic law, and shows potential improvements in zakat distribution to provide greater social and economic impact for mustahik.